Gaps in the thread: Disease, production, and opportunity in the failing silk industry of South Sulawesi - Nuraeni, Sitti (Forest and Society, 2017)
Indonesian silk farming (Sericulture) has experienced two waves of a pebrine epidemic (also known as pepper disease) and grasserie. The first pebrine epidemic occurred in 1973 and the second one occurred in 2010. Natural silk production in Indonesia has undergone dramatic decline after these epidemics. In addition to the disease, other factors also simultaneously contributed to the decline. This research examines the conditions and challenges to national natural silk industry recovery after a pebrine epidemic. The present study employs a survey and focus group discussion in three regencies (Wajo, Soppeng, and Enrekang), which took place in September 2016. Findings show that there are three major factors which contribute to the decline of national silk production, namely the: i) epidemic of silkworm disease, ii) quality of silkworms and the process of silkworm provision, iii) insufficiency of farmer means of production, and iv) lack of guidance and assistance for the farmers. Without interventions and greater support to properly maintain silkworm operations a potentially lucrative economy for rural farmers could go unrealized. The implications of this research also highlight key potential interventions for working with communities and supporting the overall resilience of national silk production in Indonesia.